The processing characteristics of Nigerian pigeon pea (Cajanus cajan L.) - Okpala, Mary Ozioma (2018)
This study sorts to improve the utilisation of pigeon pea as a ready-to-eat expanded snack food by investigating it’s processing characteristics under different environments. Existing literature suggests that pigeon peas, as reported for other legumes, could be difficult to cook due to their lack of hydration and the time required for softening during heating. These difficulties were attributed to the presence of seed coat, cell wall materials and some anti-nutritional factors. During these studies, the physicochemical characteristics of three commercial varieties of Nigerian pigeon pea (white Agatu, red Agatu and Bayelsa) were determined to select a variety appropriate for development of a snack. A high specific density (1.26 g/ml) of the seed suggested that the seeds’ native matrix and components are densely packed with limited voids between structures. Among the findings of this study include contrary to the earlier reports, that the hard to cook textural defect of pigeon pea was equally because of the presence of the seed coat and cell wall, the seed coat did not show to have posed any difficulty in the hydration of the seed. The seed coat easily detached from the cotyledon within 30 minutes of soaking in water after taking its own weight in water. However, the cotyledon weight only increased by 29%. Although soaking and dehulling altered the chemical composition of the seed but the protein, starch and fibre content still showed appropriate values for the production of healthy snacks. As no significant differences (P<0.05) in the key physicochemical characteristics were observed for the different varieties and due to economic considerations, white Agatu was selected for further study. To increase accessibility of starch to water, several treatments were applied, either targeting hydration or softening of the seed. In contrast to conventional soaking, hydration without stirring at 37-90 °C for 4 hours revealed three stages of hydration with water uptake levels being similar, but reaching the maximum hydration at different times (120-150 min) depending on the temperature. Cell wall degradation was affected by mild shear and heat, with or without alkaline solutions and enzymes that degrade cell walls. Results showed an improved swelling in excess water of treated milled material suggesting the positive influence of such treatments. For most treated samples, the thermal and crystallinity properties evaluated with Differential Scanning Calorimeter (DSC) and Wide-Angle X-Ray Diffractometer confirmed intact starch crystalline structures. This indicated the robustness and thermostability of pigeon pea. Since the treatments did not cause sufficient change in the hydrated seeds, a severe treatment (thermomechanical extrusion) using high shear and temperatures was used. The twin screw thermomechanical extrusion was adopted to ensure changes in the native chemical components and cellular structures of pigeon pea. Extrusion of treated and non-treated pigeon pea allowed expanded ready-to-eat snack products to be developed that were influenced by extrusion conditions and feed type. Optimised extrusion conditions (11% feed moisture, 14 kg feed rate, 150 °C die temperature and screw speed of 400 rpm) provided maximum torque and caused high levels of starch conversion and positive extrudate quality. Although this has not been reported in literature, the intensity of an X-Ray diffraction peak at 340 2-Theta (proposed to be globoid crystals of phytic acid salt; an anti-nutritional factor) which was detected in all the seed powdered samples was reduced after the extrusion process. From microscopy and other analyses, it was inferred that for an expanded snack, most of the structural entities that occurred in the seed needed to be eradicated and a homogenous melt favoured formation of well expanded and stable extrudates. Given the above processes applied, it is recommended that white Agatu pigeon pea be used to create extruded snack product in a safe and economic way. Keywords: pigeon pea, cell wall, starch, hydration, swelling, structural degradation and extrusion.